Development and Characterization of Hand Sanitizer Containing Lempuyang Emprit (Zingiber amaricans BL.) Essential Oil With Zerumbone as The Main Chemical Component - Ariani, Sri Retno Dwi; Mulyani, Sri; Susanti Vh, Elfi; Utomo, Suryadi Budi; Wathon, Muhammad Hizbul; Pramesti, Anastasia Diaz (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
Recently, research on the chemistry of natural products as medicinal has been increasingly developed; this is because natural products have many chemical components, have the potential biological activities without side effects, and are easy to obtain. One of these natural products is Lempuyang Emprit (Zingiber amaricans BL.) essential oil. The researchers guided UKM Suti Sehati to develop a new product: a hand sanitizer containing Lempuyang Emprit essential oil (LEEO). This study aims to make ten hand sanitizer formulas by varying LEEO concentrations and determine the best formula based on the physical properties and antibacterial activities. The best formulation obtained was then optimized with variations in fragrance concentration. The best product was selected by a hedonic test using 30 untrained panelists based on the parameters of color, scent, texture, pH, homogeneity, speed of drying, causing no red skin, causing no pain, and causing no dry skin. The antibacterial activity tests were performed against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922 using the disk method. The LEEO isolation was carried out using steam and water distillation methods, and the chemical components of the best product was identified using the GC-MS method. Based on the hedonic test, the best hand sanitizer product contains 1.5% LEEO and 3% fragrance. This product has a strong antibacterial activity value against S. aureus ATCC 25923, with an inhibition zone of 15.95 mm, and a moderate value against E. coli ATCC 25922, with an inhibition zone of 9.42 mm. The hand sanitizer product contains 21.35% of Zerumbone and exhibits antibacterial and antioxidant capabilities.